2005
DOI: 10.1111/j.1440-1738.2004.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Fractal size and spatial distributions of fault zones: An investigation into the seismic Chelungpu Fault, Taiwan

Abstract: The fractality of fault zones of thickness T for the 248-m-long core from a borehole penetrating the northern segment of the seismic Chelungpu Fault, Taiwan, was analyzed. The frequency curve of T shows that the fractal dimension is normal when T is smaller than a characteristic thickness T c , and it becomes abnormally large when T exceeds T c . The fractal dimensions of size and spatial distributions of T increase as the mean distribution density of T increases, which is inconsistent with the evolution laws … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Before we extrapolate the obtained fault data to the unsurveyed area, we have to confirm the constant scaling properties (fractal geometry) of faults are satisfied in the study area. Cello et al (2000) and Otsuki et al (2005) confirmed that the linear relationships between cumulative number and fault width in a range of 2-3 orders of magnitude on log-log diagrams, which indicating self-similar (scale independent) properties of the faults. The faults in the Inobuseyama area also show a linear relationship between cumulative fault number and fault width (Fig.…”
Section: Slip Rate In the Nktzsupporting
confidence: 61%
“…Before we extrapolate the obtained fault data to the unsurveyed area, we have to confirm the constant scaling properties (fractal geometry) of faults are satisfied in the study area. Cello et al (2000) and Otsuki et al (2005) confirmed that the linear relationships between cumulative number and fault width in a range of 2-3 orders of magnitude on log-log diagrams, which indicating self-similar (scale independent) properties of the faults. The faults in the Inobuseyama area also show a linear relationship between cumulative fault number and fault width (Fig.…”
Section: Slip Rate In the Nktzsupporting
confidence: 61%
“…This value of P max is enough for the formation of the clayey veins. This process is discussed in greater detail in Otsuki et al . (2005).…”
Section: Implications Of Fault Rocks and Their Structures For Fault Smentioning
confidence: 99%